1997
DOI: 10.2337/diacare.20.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Islet Autoantibodies in Patients With Gestational Diabetes Mellitus

Abstract: Low-titer ICAs and IAAs are not infrequent in pregnant women, but multiple islet autoantibodies and antibodies to GAD65 or IA-2 were not found in GDM. These findings suggest that the serological characteristics of IDDM are rare in GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 0 publications
6
39
0
1
Order By: Relevance
“…This finding is consistent with a series of studies performed in Finnish [57], other Scandinavian [59], Italian [60,61], German [62] and US [63] women with GDM. These studies link the given polymorphism to the disease with a reported frequency of the polymorphism varied from 2.2% to 9.5%.…”
Section: Gad65absupporting
confidence: 95%
“…This finding is consistent with a series of studies performed in Finnish [57], other Scandinavian [59], Italian [60,61], German [62] and US [63] women with GDM. These studies link the given polymorphism to the disease with a reported frequency of the polymorphism varied from 2.2% to 9.5%.…”
Section: Gad65absupporting
confidence: 95%
“…The frequency of ICAs found in this study lies within the prevalence range of 1.6-12.4% previously reported by others (6,7,(24)(25)(26)(27)30), using standardized immunofluorescence techniques. As for GADAs, the prevalence in the GDM-A subgroup (5.4%) was similar, compared with a Caucasian GDM-A population from Spain (6%) (28), but higher, compared with two GDM-A populations from Denmark (2.2%) (29) and Northern Italy (0%) (27). Possible reasons for this variability may be differences in the ethnic origin of the patient populations, differences in the criteria used for the diagnosis of GDM, and differences in the control population used to establish the normal range of antibodies in pregnancy.…”
Section: Discussionsupporting
confidence: 62%
“…In contrast, Dozio et al [6] observed only low frequencies of islet cell autoimmunity (ICA, insulin autoantibody [IAA]) among GDM patients, similar to the prevalence found in women with normal glucose tolerance. None of Gestational diabetes mellitus (GDM) is a heterogeneous entity, including carbohydrate intolerance of variable severity with onset or first recognition during pregnancy.…”
Section: Pathogenesis Of Gdmmentioning
confidence: 66%